The knot - Watson, Mark (London : Simon & Schuster, 2013)
Dominic Kitchen is a wedding photographer. Every Saturday since his career began in the sixties he has photographed a bride and groom on the happiest day of their lives, captured the moment they tied the knot forever, and then faded away into the background.
Keywords: Photographers -- Fiction; Fiction